PC (personal computing) banking system to Core Banking System (CBS) : a case study based on United Commercial Bank Ltd. - Ahmed, Nasim (BRAC University, 2015)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2015